2014
DOI: 10.3109/0886022x.2014.991327
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effect of aliskiren on renal ischemia/reperfusion injury in rats: electron microscopy and molecular study

Abstract: (2015) Renoprotective effect of aliskiren on renal ischemia/reperfusion injury in rats: electron microscopy and molecular study, Renal Failure, 37:2,[343][344][345][346][347][348][349][350][351][352][353][354] Purpose: To determine the protective effect of aliskiren on ischemia-reperfusion (I/R) injury in a rat renal (I/R) model. Methods: Rats were randomly divided into five groups: sham control group; sham control with aliskiren pretreatment; I/R group and I/R with two doses of aliskiren pretreatment. Rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 65 publications
8
17
0
1
Order By: Relevance
“…Therefore, the suppression of the RAAS with aliskiren in the paracetamol‐induced hepatotoxicity group could reduce the oxidative stress‐induced damage. Earlier studies performed with captopril and aliskiren showed that inhibition of Ang II reduced the production of free oxygen radicals [He et al, ; Ziypak et al, ]. Our previous studies showed that aliskiren protects against oxidative stress [Akpinar et al, ; Ziypak et al, ], which is consistent with our results on paracetamol toxicity.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, the suppression of the RAAS with aliskiren in the paracetamol‐induced hepatotoxicity group could reduce the oxidative stress‐induced damage. Earlier studies performed with captopril and aliskiren showed that inhibition of Ang II reduced the production of free oxygen radicals [He et al, ; Ziypak et al, ]. Our previous studies showed that aliskiren protects against oxidative stress [Akpinar et al, ; Ziypak et al, ], which is consistent with our results on paracetamol toxicity.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also support these findings. Furthermore, aliskiren treatment increases the SOD activity of kidneys in renal ischemia/reperfusion injury showing high antioxidant properties [Ziypak et al, ]. Similar to this study, aliskiren treatment increased SOD activity in low dose.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations